Christine de Pizan in Bruges le Livre de la Cité des Dames as Het Bouc van de Stede der Vrauwen (London, British Library, Add. 20698) - Lie, Orlanda Soei Han 1949-; Meuwese, Martine 1966-; Aussems, Mark; Joldersma, Hermina (Middeleeuwse studies en bronnen, 2015)
Christine de Pizan composed her famous defense of women, Le Livre de la Cité des Dames, as a response to the misogynistic writings of the time. She used the allegorical form to present the life and deeds ofvirtuous women as the metaphorical building blocks for the City ofLadies. In 1475, some forty-five years after Christine's death, Jan de Baenst, a descendant of a prominent Bruges family, ordered a translation. Het Bouc van de Stede der Vrauwen is the only Middle Dutch translation of a work by Christine de Pizan and it has survived in only one manuscript. Christine de Pizan in Bruges tells the story of this unique codex by focusing on the background of the commissioner, the codicological aspects, the highly original but unfinished illumination program, the 41 miniatures executed are reproduced here in full colour, and the translator's personal epilogue